Effect of netting direction and number of meshes around on size selection in the codend for Baltic cod (Gadus morhua) - Wienbeck, Harald; Herrmann, Bent; Moderhak, Waldemar; Stepputtis, Daniel (Fisheries Research, 2011)
We investigated experimentally the effect that turning the netting direction 90? (T90) and halving the number of meshes around in the circumference in a diamond mesh codend had on size selection of Baltic cod. The results generally agreed with predictions of a previous simulation-based study. Both modifications had a significant positive effect on the size selection of cod. The best selection results were obtained for a codend in which both factors were applied together. For that codend, very little between-haul variation in cod size selection was detected, especially compared to the reference codend in which none of the modifications were applied.